Use of morphological, biochemical and molecular markers for early identification of an interspecific cucurbit hybrid (Cucurbita maxima x Cucurbita moschata) = Uso de marcadores morfológicos, bioquímicos y moleculares para la identificación de híbridos interespecíficos (Cucurbita maxima x Cucurbita moschata) de zapallo - Tarnowski, Christian; Valdez, Jorge Gustavo; Lorello, Ines Maria; Barboza Rojas, Karina; Cavagnaro, Pablo; Della Gaspera, Pedro (ASAHO, 2022)
Aconcagua INTA is an Argentine widespread cucurbit cultivar with high yield and suitability for the dehydration industry, developed from an interspecific cross (Cucurbita maxima x Cucurbita moschata). Its seed production involves the use of etephon in the maternal progenitor to castrate male flower organs, while the other line serves a pollen donor. Because this process is not totally effective, some hermaphrodite flowers remain in the maternal line, leading to self-pollination and –therefore- seeds of non-hybrid origin, which are phenotypically different from the hybrid. Thus, the percentage of non-hybrid seeds needs to be estimated and labelled in commercial seed lots of this cultivar. To this end, the present study analyzed, comparatively, morphological, biochemical and molecular markers that may be used for the early identification of this hybrid and its parental lines. Thus, a morphological marker based on leaf characteristics, protein profiles by UTLIEF, and the microsatellite molecular marker CMBR22, were evaluated in hybrid and parental plants. All three marker systems were able to accurately identify the hybrid and the parental lines, with results revealing 100% correspondence among the three types of markers. The protein and molecular markers developed herein represent a valuable tool for the early identification of hybrids in seed lots of cv. Aconcagua INTA.